High-entropy anti-ferroelectric ceramic material with high energy storage performance as well as preparation method and application of high-entropy anti-ferroelectric ceramic material

By introducing a variety of ions into the A-position of the perovskite structure for high-entropy design, and using component control methods, high-entropy antiferroelectric ceramic materials are prepared, which solves the problem of insufficient energy storage density and efficiency of existing antiferroelectric ceramic materials, and achieves high electrical resistance and energy storage performance.

CN119775004AActive Publication Date: 2025-04-08SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411990141.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing antiferroelectric ceramic materials have shortcomings in energy storage density and energy storage efficiency, especially under the huge differences in positive and negative turning electric fields, which show significant electrical hysteresis, resulting in lower energy storage efficiency and density.

Method used

Through a high-entropy design strategy, six ions of different radius and valence states were introduced into the A position of the perovskite structure to prepare high-entropy antiferroelectric ceramic materials, and the antiferroelectricity of the ceramics was regulated through component regulation methods to improve energy storage density and efficiency.

Benefits of technology

High energy storage density and high energy storage efficiency are achieved, which are specifically manifested as breakdown electric field between 527 and 878 kV/cm, energy storage density is 7.1 to 10.9 J/cm3, energy storage efficiency is 81.1% to 87.5%, and at the same time, the relaxation characteristics and electrical resistance of the ceramic are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775004A_ABST
    Figure CN119775004A_ABST
Patent Text Reader

Abstract

The invention relates to a high-entropy anti-ferroelectric ceramic material with high energy storage performance as well as a preparation method and application of the high-entropy anti-ferroelectric ceramic material. The composition chemical formula of the high-entropy anti-ferroelectric ceramic material is (Sr < 0.2 > Ca < 0.2 > Pb < 0.2 > Bi < 0.2-x > La < x > Na < 0.2 >) TiO3, wherein x is greater than 0 and less than 0.20. The high-entropy antiferroelectric ceramic is successfully designed and obtained for the first time, has excellent high energy storage efficiency and high energy storage density, and is widely applied to multilayer ceramic capacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional ceramics, and relates to a high-entropy antiferroelectric ceramic material with high energy storage performance, a preparation method and an application thereof. Background Art

[0002] High-performance energy storage capacitors based on dielectric materials are an important component of advanced high-power / pulse power electronic systems. Dielectric capacitors have the highest power density, ultra-fast charge and discharge rates, and long working life due to their unique electrostatic energy storage mechanism. Therefore, they have been widely used in various high-tech fields, including medical equipment, military equipment, and hybrid electric vehicles. The energy storage performance of dielectric capacitors mainly depends on their dielectric layer, but the low energy density of commercial dielectric materials has seriously hindered their wider application and the development trend towards miniaturization, lightweight, and low cost. The dielectric materials used as pulse capacitors are mainly linear ceramics, ferroelectric ceramics, and antiferroelectric ceramics. Among them, antiferroelectric ceramics are considered to be the most promising materials for pulse power capacitors due to their high saturation polarization and low remnant polarization. However, due to the huge difference between the positive and negative transition electric fields, antiferroelectrics exhibit significant electrical hysteresis, which greatly reduces the energy storage efficiency and energy storage density. Therefore, it is of great significance to develop antiferroelectric ceramic materials with both high energy storage density and energy storage efficiency.

[0003] Recent studies have shown that the high entropy strategy is an effective and flexible method to improve the physical properties of ferroelectrics. It has become a new way to promote dielectric energy storage through its fine design of local polarization configurations and other intrinsic effects caused by entropy increase, such as high entropy stable phase structure, lattice disorder, lattice distortion inhibiting grain coarsening, improved mechanical properties, cocktail effect, etc. For example, by introducing multiple elements at the A and B positions of the perovskite structure, polymorphic local distortion is induced, resulting in ultra-small polar nano-regions, enhanced breakdown electric fields and delayed polarization saturation, which significantly improves the energy storage performance of potassium sodium niobate-based ferroelectric ceramics (reference: Nat. Commun., 2022, 13(1), 3089.). Some researchers have also introduced multiple elements at equal molar ratios at the Bi and Ti positions of the pyrochlore structure, using configuration entropy as a quantitative evaluation index of local composition inhomogeneity (relaxation characteristics), and achieved excellent energy storage performance through fine design of entropy (references: Nat. Mater., 2022, 21, 1074–1080., Nat. Energy, 2023, 14, 956–964.). Coincidentally, researchers introduced five elements at equal molar ratios at the A position of the tungsten bronze structure, and used the high disorder and lattice distortion introduced by the high entropy strategy to enhance the relaxation characteristics and electrical strength, achieving excellent energy storage performance (reference: Nat. Commun., 2024, 15 (1), 5232.). At present, the research and development of high-entropy ceramics is mostly focused on linear ceramics and ferroelectric ceramics, and no high-entropy antiferroelectric ceramic system has been reported. If high-entropy design methods can be used to develop high-entropy antiferroelectric ceramics, there will be hope of obtaining antiferroelectric ceramic materials with relaxation properties, thereby achieving comprehensive properties such as high electrical strength, energy storage density and energy storage efficiency. The concept of high-entropy design can provide new ideas for the design and development of high-performance antiferroelectric ceramic materials. Summary of the invention

[0004] In view of the above problems, the present invention takes into account the effectiveness of high entropy strategy in designing high-performance dielectric energy storage ceramic materials, and successfully designs and obtains high entropy antiferroelectric ceramics for the first time. The purpose of the present invention is to provide a high entropy antiferroelectric ceramic material with high energy storage performance, and its preparation method and application.

[0005] In a first aspect, the present invention provides a high entropy antiferroelectric ceramic material with high energy storage performance, wherein the composition chemical formula of the high entropy antiferroelectric ceramic material is: (Sr 0.2 Ca 0.2 Pb 0.2 Bi 0.2-x La x Na 0.2 )TiO3, where 0<x<0.20.

[0006] Preferably, x=0.10-0.16; more preferably, x=0.14.

[0007] The present invention adopts the strategy of A-site high entropy design to introduce 6 ions of different radii and valence states into the A-site of the perovskite structure to prepare high entropy antiferroelectric ceramics, and further utilizes the component regulation method to regulate the antiferroelectricity of the ceramic material and obtain higher energy storage density and efficiency.

[0008] Preferably, the configuration entropy ΔS of the high entropy antiferroelectric ceramic material mix ≥1.61R.

[0009] Preferably, the breakdown electric field of the high entropy antiferroelectric ceramic material is 527-878 kV / cm.

[0010] Preferably, the recyclable energy storage density of the high entropy antiferroelectric ceramic material is 7.1-10.9 J / cm 3 .

[0011] Preferably, the energy storage efficiency of the high entropy antiferroelectric ceramic material is 81.1% to 87.5%.

[0012] In a second aspect, the present invention provides a method for preparing a high entropy antiferroelectric ceramic material with high energy storage performance, comprising: (1) using strontium carbonate powder, calcium carbonate powder, lead oxide powder, bismuth oxide powder, lanthanum oxide powder, sodium carbonate powder, and titanium dioxide powder as raw materials, weighing and mixing according to the stoichiometric ratio of high entropy antiferroelectric ceramic materials, and pre-sintering to obtain ceramic powder; (2) grinding the obtained ceramic powder, adding a binder, and granulating, sieving and molding to obtain a ceramic green body; (3) The obtained ceramic green body is subjected to plastic disassembly and sintering to obtain the high entropy antiferroelectric ceramic material.

[0013] Preferably, in step (1), the mixing method is ball milling; the parameters of the ball milling include: anhydrous ethanol as the ball milling medium, a ball milling speed of 200 to 240 rpm, and a time of 4 to 6 hours; The temperature of the pre-sintering treatment is 900-1000° C., the time is 2-3 hours, and the heating rate is 1-3° C. / min.

[0014] Preferably, in step (2), the binder is a polyvinyl alcohol aqueous solution with a concentration of 6 to 7 wt.%; the amount of the binder added is 6 to 7 wt.% of the mass of the ceramic powder; The parameters of the fine grinding include: anhydrous ethanol as the ball milling medium, a rotation speed of 200 to 240 rpm, and a time of 4 to 6 hours; The sieve used for screening is 40 mesh.

[0015] Preferably, in step (3), the temperature of the plastic removal is 750-850°C, and the time is 2-3 hours; preferably, the temperature of the plastic removal is 800°C, and the time is 2 hours.

[0016] Preferably, in step (3), the sintering parameters include: a sintering temperature of 1100-1200°C, a sintering time of 2-3 hours, and a heating rate of 1-3°C / min; preferably, the sintering heating rate is 2°C / min.

[0017] In a third aspect, the present invention provides an energy storage ceramic element, comprising: a high-entropy antiferroelectric ceramic material with high energy storage performance, and electrodes distributed on the surface of the high-entropy ceramic material.

[0018] In a fourth aspect, the present invention provides an application of a high-entropy antiferroelectric ceramic material with high energy storage performance in a multilayer ceramic capacitor (Multi-Layer Ceramic Capacitor, MLCC).

[0019] Beneficial effects: In the present invention, (Sr 0.2 Ca 0.2 Pb 0.2 Bi 0.2-x La x Na 0.2 )TiO3 (0<x<0.20) high entropy antiferroelectric ceramic material. The high disorder introduced by high entropy enhances the relaxation characteristics and promotes the formation of small-sized polar nanodomains, so that the hysteresis loop of the ceramic is refined, which is conducive to obtaining high energy storage efficiency; strong lattice distortion refines the grains, enhances the electrical strength, and is conducive to obtaining high energy storage density. Furthermore, the antiferroelectricity of the ceramic is regulated by the method of component regulation to achieve the best energy storage characteristics. The present invention has a simple preparation process and excellent energy storage performance, and is suitable for the preparation and application of multilayer capacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the X-ray diffraction pattern of the ceramic materials prepared in Examples 1-4 and Comparative Examples 1 and 2; Figure 2 is a surface microscopic morphology of the high entropy antiferroelectric ceramic material in Example 1; Figure 3 is a surface microscopic morphology of the high entropy antiferroelectric ceramic material in Example 2; Figure 4 is a surface microscopic morphology of the high entropy antiferroelectric ceramic material in Example 3; Figure 5 is a surface microscopic morphology of the high entropy antiferroelectric ceramic material in Example 4; Figure 6is the dielectric temperature spectrum of the high entropy antiferroelectric ceramic material in Example 1; Figure 7 is the dielectric temperature spectrum of the high entropy antiferroelectric ceramic material in Example 2; Figure 8 is the dielectric temperature spectrum of the high entropy antiferroelectric ceramic material in Example 3; Fig. 9 is the dielectric temperature spectrum of the high entropy antiferroelectric ceramic material in Example 4; Fig.10 are bipolar hysteresis loop diagrams of the high entropy antiferroelectric ceramic materials in Examples 1-4 and Comparative Examples 1 and 2; Fig.11 is a current curve diagram of the high entropy antiferroelectric ceramic material in Examples 1-4 and Comparative Examples 1 and 2; Fig.12 It is a unipolar hysteresis loop diagram of the high entropy antiferroelectric ceramic material in Examples 1-4 and Comparative Examples 1 and 2; Fig.13 This is a surface microscopic morphology of the high entropy ceramic material in Comparative Example 1; Fig.14 This is a surface microscopic morphology of the high entropy ceramic material in Comparative Example 2; Fig.15 is the dielectric temperature spectrum of the high entropy ceramic material in Comparative Example 1; Fig.16 is the dielectric temperature spectrum of the high entropy ceramic material in Comparative Example 2; Fig.17 It is a comparison chart of the energy storage performance of the high entropy antiferroelectric ceramic materials in Examples 1-4 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0021] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.

[0022] First, the present invention provides a high entropy antiferroelectric ceramic with high energy storage performance, wherein the composition chemical formula of the high entropy antiferroelectric ceramic material is: (Sr 0.2 Ca 0.2 Pb 0.2 Bi 0.2-x La x Na 0.2 )TiO3, where 0<x<0.20. The present invention obtains high entropy antiferroelectric ceramics for the first time through high entropy design of multiple elements at the A position. Specifically, the present invention is based on the antiferroelectric genes of calcium strontium titanate and sodium bismuth titanate, and introduces highly polarized Pb2+ , introduce La 3+ To stabilize the antiferroelectricity, in an equal molar ratio (where Bi 3+ and La 3+ The total accounts for 20%) to design high entropy antiferroelectric components and further increase La 3+ The content can be adjusted to regulate the antiferroelectricity, thereby achieving the optimal comprehensive energy storage performance.

[0023] The configuration entropy of the high entropy antiferroelectric ceramic material prepared by the present invention is △S mix ≥1.61R; the breakdown electric field of the high entropy antiferroelectric ceramic material is 527-878 kV / cm; the recyclable energy storage density of the high entropy antiferroelectric ceramic material is 7.1-10.9 J / cm 3 The energy storage efficiency of the high entropy antiferroelectric ceramic material is 81.1% to 87.5%. The electric field-current curve of the high entropy antiferroelectric ceramic material has antiferroelectricity with four current peaks, and a reversible antiferroelectric-ferroelectric phase transition occurs at the turning electric field; the high entropy antiferroelectric ceramic material has relaxation characteristics of a slender hysteresis loop.

[0024] In the present invention, the high entropy antiferroelectric ceramic material is prepared by a solid phase method, and the process flow is simple. The following is an exemplary description of the preparation method of the high entropy antiferroelectric ceramic material with high energy storage performance provided by the present invention.

[0025] Strontium carbonate powder, calcium carbonate powder, lead oxide powder, bismuth oxide powder, lanthanum oxide powder, sodium carbonate powder and titanium dioxide powder are used as raw materials, weighed and mixed according to the stoichiometric ratio of high entropy antiferroelectric ceramic materials, and pre-sintered to obtain ceramic powder.

[0026] In an optional embodiment, the mixing method is ball milling; the parameters of the ball milling include: anhydrous ethanol as the ball milling medium, a rotation speed of 200 to 240 rpm, and a time of 4 to 6 hours.

[0027] In an optional embodiment, the pre-sintering treatment is performed at a temperature of 900 to 1000° C., for 2 to 3 hours, and at a heating rate of 1 to 3° C. / min (eg, 2° C. / min).

[0028] The obtained ceramic powder is finely ground, a binder is added, and the powder is granulated, sieved and molded to obtain a ceramic green body.

[0029] In an optional embodiment, the parameters of the fine grinding include: anhydrous ethanol as the ball milling medium, a rotation speed of 200 to 240 rpm, and a time of 4 to 6 hours. The sieve is a 40-mesh screen. The binder is a polyvinyl alcohol aqueous solution with a concentration of 6 to 7 wt.%; the amount of the binder added is 6 to 7 wt.% of the mass of the ceramic powder.

[0030] The obtained ceramic green body is subjected to plastic disassembly and sintering to obtain the high entropy antiferroelectric ceramic material.

[0031] In an optional embodiment, the temperature of the plastic discharge is 750-850°C, and the time is 2-3 hours; preferably, the temperature of the plastic discharge is 800°C, and the time is 2 hours.

[0032] In an optional embodiment, the obtained ceramic body is covered with the obtained ceramic powder and sintered under closed conditions. The sintering parameters include: a sintering temperature of 1100-1200°C, a sintering time of 2-3 hours, and a heating rate of 1-3°C / min; preferably, the sintering heating rate is 2°C / min.

[0033] In the present invention, the high entropy antiferroelectric ceramic material has a simple composition, a simple preparation process, and has the characteristics of high breakdown strength, high energy storage density, and high energy storage efficiency, and is suitable for the preparation and application of dielectric capacitors in pulse power capacitor devices.

[0034] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0035] Example 1

[0036] The preparation process of the high entropy antiferroelectric ceramic material with high energy storage performance provided in this embodiment 1 comprises the following steps: (1) According to the molecular formula (Sr 0.2 Ca 0.2 Pb 0.2 Bi 0.2-x La x Na 0.2 )TiO3 (x = 0.10) is used for batching calculation. The raw materials used include SrCO3, CaCO3, Pb3O4, Bi2O3, La2O3, Na2CO3, and TiO2. They are weighed with an electronic balance with an accuracy of 0.001g. The purity of the raw material powders is higher than 99.0%; (2) The weighed raw materials are mixed and placed in a nylon jar, and anhydrous ethanol is added to the jar to a level not higher than 2 / 3 of the jar height. The nylon jar is placed on a planetary ball mill with zirconium oxide balls as the medium and mixed for 6 hours (the particle size of the zirconium oxide balls used is 6 mm and 10 mm); then the raw materials are poured out and dried in an oven, and then sieved with a 40-mesh nylon sieve, and the sieved mixed powder is pressed into a cylinder with a size of 15 mm in diameter and 2 mm in height on a press; in an air atmosphere, the mixed powder is pre-calcined at 900° C. for 2 hours, and then crushed through a 40-mesh sieve to obtain a ceramic powder; (3) placing the obtained ceramic powder in a stirred mill and further grinding the ceramic powder using a zirconium ball with a diameter of 1 mm for 6 hours, and then pouring it out and drying it in an oven; (4) adding a 6 wt % polyvinyl alcohol aqueous solution to the finely ground ceramic powder, wherein the amount of the polyvinyl alcohol aqueous solution added is 6.5 % of the mass of the ceramic powder, and then granulating the powder evenly, passing through a 40-mesh sieve, and pressing the powder into a small cylindrical ceramic green body with a size of 13 mm in diameter and 1 mm in height; (5) placing the obtained ceramic green body in a muffle furnace cavity for plastic discharge at a temperature of 800° C. for 2 hours, and taking out the plastic discharge sample after naturally cooling to room temperature; (6) The molded green body is placed in an alumina crucible and covered with ceramic powder for closed sintering at a sintering temperature of 1160° C. for 2 hours. After naturally cooling to room temperature, the sample is taken out to obtain a high entropy antiferroelectric ceramic material.

[0037] The high entropy antiferroelectric ceramic prepared in Example 1 was subjected to an X-ray diffraction test. The test results are as follows: Figure 1 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 1 has no impurity phase and is a single-phase perovskite structure.

[0038] The surface morphology of the ceramic obtained in Example 1 was photographed after surface treatment. Figure 2 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 1 has a dense surface, uniformly distributed large and small grains, a grain size of about 1.84 μm, and no impurities.

[0039] The ceramic obtained in Example 1 was ground and polished on both sides, and silver electrodes were coated on both sides of the ceramic by screen printing and silver was fired at 650° C. for 30 min. After cooling to room temperature, the dielectric properties were tested. The test results are as follows: Figure 6 As shown in the figure, it can be seen that the dielectric peak of the high entropy antiferroelectric ceramic prepared in Example 1 is broadened and the frequency dispersion phenomenon is obvious, and it has strong relaxation characteristics.

[0040] The ceramic obtained in Example 1 was ground and polished on both sides, and the ferroelectric performance was tested using ion sputtering gold-plated electrodes. The test results are shown in Fig.10As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 1 has a typical antiferroelectric double hysteresis loop. Fig.11 The current curve of the high entropy antiferroelectric ceramic obtained in Example 1 is shown. As can be seen from the figure, there are two obvious current peaks corresponding to the positive and negative turning electric fields, which further confirms the antiferroelectricity of the high entropy antiferroelectric ceramic obtained in Example 1. Fig.12 The unipolar hysteresis loop of the high entropy antiferroelectric ceramic obtained in Example 1 is shown. As can be seen from the figure, the breakdown field strength of the high entropy antiferroelectric ceramic obtained is 527 kV·cm -1 , the energy storage density is 7.1 J·cm -3 , the energy storage efficiency is 81.1%.

[0041] Example 2

[0042] The preparation process of the high entropy antiferroelectric ceramic material with high energy storage performance provided in this embodiment 2 refers to that of embodiment 1, with the only difference being that: x=0.12; in step (6), the sintering temperature is 1140°C.

[0043] The high entropy antiferroelectric ceramic prepared in Example 2 was subjected to an X-ray diffraction test. The test results are as follows: Figure 1 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 2 has no impurity phase and is a single-phase perovskite structure.

[0044] The surface morphology of the ceramic obtained in Example 2 was photographed after surface treatment. Figure 3 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 1 has a dense surface, uniformly distributed large and small grains, a grain size of about 1.25 μm, and no impurities.

[0045] The ceramic obtained in Example 2 was ground and polished on both sides, and silver electrodes were coated on both sides of the ceramic by screen printing and silver was fired at 650°C for 30 minutes. After cooling to room temperature, the dielectric properties were tested. The test results are as follows: Figure 7 As shown in the figure, it can be seen that the Curie temperature of the high entropy antiferroelectric ceramic prepared in Example 2 is further reduced, the dielectric peak is broadened and the frequency dispersion phenomenon is aggravated, indicating that the relaxation characteristics are enhanced.

[0046] The ceramic obtained in Example 2 was ground and polished on both sides, and the ferroelectric performance was tested using ion sputtering gold-plated electrodes. The test results are shown in Fig.10 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 2 exhibits an antiferroelectric double hysteresis loop. Fig.11 The current curve of the high entropy antiferroelectric ceramic obtained in Example 2 is shown. As can be seen from the figure, there are two obvious current peaks corresponding to the positive and negative turning electric fields, which confirms the antiferroelectricity of the high entropy antiferroelectric ceramic obtained in Example 2. Fig.12The unipolar hysteresis loop of the high entropy antiferroelectric ceramic obtained in Example 2 is shown. As can be seen from the figure, the breakdown field strength of the high entropy antiferroelectric ceramic obtained is 629 kV·cm -1 , the energy storage density is 9.0 J·cm -3 , the energy storage efficiency is 83.0%.

[0047] Example 3

[0048] The preparation process of the high entropy antiferroelectric ceramic material with high energy storage performance provided in this embodiment 3 refers to that of embodiment 1, with the only difference being that: x=0.14; in step (6), the sintering temperature is 1120°C.

[0049] The high entropy antiferroelectric ceramic prepared in Example 3 was subjected to an X-ray diffraction test. The test results are as follows: Figure 1 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 3 has no impurity phase and is a single-phase perovskite structure.

[0050] The surface morphology of the ceramic obtained in Example 3 was photographed after surface treatment. Figure 4 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 3 has a dense surface, uniformly distributed large and small grains, a grain size of about 1.16 μm, and no impurities.

[0051] The ceramic obtained in Example 3 was ground and polished on both sides, and silver electrodes were coated on both sides of the ceramic by screen printing and silver was fired at 650°C for 30 minutes. After cooling to room temperature, the dielectric properties were tested. The test results are as follows: Figure 8 As shown in the figure, it can be seen that the Curie temperature of the high entropy antiferroceramic prepared in Example 3 is further reduced.

[0052] The ceramic obtained in Example 3 was ground and polished on both sides, and the ferroelectric performance was tested using ion sputtering gold-plated electrodes. The test results are shown in Figure 2. Fig.10 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 3 has an antiferroelectric double hysteresis loop, and the relaxation characteristics are significantly enhanced. Fig.11 The current curve of the high entropy antiferroelectric ceramic obtained in Example 3 is shown. As can be seen from the figure, there are two obvious current peaks corresponding to the positive and negative turning electric fields, which further confirms the antiferroelectricity of the high entropy antiferroelectric ceramic obtained in Example 3. Fig.12 The unipolar hysteresis loop of the high entropy antiferroelectric ceramic obtained in Example 3 is shown. As can be seen from the figure, the breakdown field strength of the high entropy antiferroelectric ceramic obtained is 878 kV·cm -1 , the energy storage density is 10.9 J·cm -3 , the energy storage efficiency is 86.2%.

[0053] Example 4

[0054] The preparation process of the high entropy antiferroelectric ceramic material with high energy storage performance provided in this embodiment 4 refers to that in embodiment 1, the only difference is that: x=0.16; in step (6), the sintering temperature is 1100°C.

[0055] The high entropy antiferroelectric ceramic prepared in Example 4 was subjected to an X-ray diffraction test. The test results are as follows: Figure 1 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 3 has no impurity phase and is a single-phase perovskite structure.

[0056] The surface morphology of the ceramic obtained in Example 4 was photographed after surface treatment. Figure 5 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 4 has a dense surface, uniformly distributed large and small grains, a grain size of about 0.94 μm, and no impurities.

[0057] The ceramic obtained in Example 4 was ground and polished on both sides, and silver electrodes were coated on both sides of the ceramic by screen printing and silver was fired at 650° C. for 30 min. After cooling to room temperature, the dielectric properties were tested. The test results are as follows: Fig. 9 As shown in the figure, it can be seen that the Curie temperature of the high entropy antiferroelectric ceramic prepared in Example 4 is further reduced.

[0058] The ceramic obtained in Example 4 was ground and polished on both sides, and the ferroelectric performance was tested using ion sputtering gold-plated electrodes. The test results are shown in Fig.10 As shown in the figure, it can be seen that the high entropy antiferroelectric ceramic prepared in Example 4 exhibits weak antiferroelectricity, and the double hysteresis loop tends to disappear. Fig.11 The current curve of the high entropy antiferroelectric ceramic obtained in Example 4 is shown. As can be seen from the figure, the two current peaks corresponding to the positive and negative turning electric fields are broadened and gradually blurred and invisible, indicating the weak antiferroelectricity of the high entropy antiferroelectric ceramic obtained in Example 4. Fig.12 The unipolar hysteresis loop of the high entropy antiferroelectric ceramic obtained in Example 4 is shown. As can be seen from the figure, the breakdown field strength of the high entropy antiferroelectric ceramic obtained is 716 kV·cm -1 , the energy storage density is 8.5 J·cm -3 , the energy storage efficiency is 87.5%.

[0059] Comparative Example 1

[0060] The preparation process of the high entropy antiferroelectric ceramic material with high energy storage performance provided in this comparative example 1 refers to that in Example 1, except that: x=0; in step (6), the sintering temperature is 1200°C.

[0061] The ceramic obtained in Comparative Example 1 was subjected to an X-ray diffraction test. The test results are as follows: Figure 1 As shown in the figure, it can be seen that the ceramic obtained in this comparative example 1 has no impurity phase and is a single-phase perovskite structure.

[0062] The surface morphology of the ceramic obtained in Comparative Example 1 was photographed after surface treatment. Fig.13 As shown in the figure, it can be seen that the ceramic obtained in this comparative example 1 is dense, the size of the grains is evenly distributed, the particle size is about 2.2μm, and there is no impurity phase.

[0063] The ceramic obtained in Comparative Example 1 was ground and polished on both sides, and silver electrodes were coated on both sides of the ceramic by screen printing and silver was calcined at 650°C for 30 minutes. After cooling to room temperature, the dielectric properties were tested. The test results are as follows: Fig.15 As shown in the figure, it can be seen that the Curie temperature of the ceramic obtained in this comparative example 1 is about 125°C, and the dielectric constant changes dramatically with temperature.

[0064] The ceramic obtained in Comparative Example 1 was ground and polished on both sides, and the ferroelectric performance was tested using ion sputtering gold-plated electrodes. Fig.10 As shown in the figure, it can be seen that the ceramic obtained in this comparative example 1 has a typical ferroelectric hysteresis loop. Fig.11 The current curve of the ceramic obtained in Comparative Example 1 is shown. It can be seen from the figure that the ceramic obtained in Comparative Example 1 has only one current peak, indicating that it has no antiferroelectricity and is a typical ferroelectric ceramic. Fig.12 The unipolar hysteresis loop of the ceramic obtained in comparative example 1 is shown. It can be seen from the figure that the breakdown field strength of the obtained ceramic is 359 kV·cm -1 , the energy storage density is 2.6 J·cm -3 , the energy storage efficiency is 69.0%.

[0065] Comparative Example 2

[0066] The preparation process of the high entropy antiferroelectric ceramic material with high energy storage performance provided in this comparative example 2 refers to that of example 1, with the only difference being that: x=0.2; in step (6), the sintering temperature is 1230°C.

[0067] The ceramic obtained in Comparative Example 2 was subjected to an X-ray diffraction test. The test results are as follows: Figure 1 As shown in the figure, it can be seen that the ceramic obtained in this comparative example 1 has no impurity phase and is a single-phase perovskite structure.

[0068] The surface morphology of the ceramic obtained in Comparative Example 2 was photographed after surface treatment. Fig.14 As shown in the figure, it can be seen that the ceramic surface obtained in Comparative Example 2 is dense, the size of the grains is evenly distributed, the particle size is about 0.52 μm, and there is no impurity phase.

[0069] The ceramic obtained in Comparative Example 2 was ground and polished on both sides, and silver electrodes were coated on both sides of the ceramic by screen printing and silver was calcined at 650°C for 30 minutes. After cooling to room temperature, the dielectric properties were tested. The test results are as follows: Fig.16 As shown in the figure, it can be seen that the dielectric constant of the ceramic obtained in Comparative Example 2 changes little with temperature, and the dielectric peak moves further to low temperature.

[0070] The ceramic obtained in Comparative Example 2 was ground and polished on both sides, and the ferroelectric performance was tested using ion sputtering gold-plated electrodes. Fig.10 As shown in the figure, it can be seen that the ceramic obtained in this comparative example 2 has a nearly linear hysteresis loop. Fig.11 The current curve of the ceramic obtained in Comparative Example 2 is shown. As can be seen from the figure, there is almost no observable current peak in Comparative Example 2, indicating that its antiferroelectricity disappears and the ceramic obtained in Comparative Example 2 is a near-linear ceramic. Fig.12 The unipolar hysteresis loop of the ceramic obtained in comparative example 1 is shown. It can be seen from the figure that the breakdown field strength of the obtained ceramic is 577 kV·cm -1 , the energy storage density is 5.4 J·cm -3 , the energy storage efficiency is 83.1%.

[0071] Figure 1 1 is an X-ray diffraction diagram of the ceramic materials prepared in Examples 1-4 and Comparative Examples 1 and 2. As can be seen from the diagram, Examples 1-4 and Comparative Examples 1 and 2 are all single-phase perovskite structures.

[0072] Figure 2-5 Surface microscopic morphology of the ceramic materials prepared in Examples 1 to 4. As can be seen from the figure, as the content of La replacing Bi increases, the grain size gradually decreases.

[0073] Figure 6-9 It is the dielectric temperature spectrum of the ceramic material prepared in Example 1 to 4. As can be seen from the figure, as the content of La replacing Bi increases, the change of dielectric constant with temperature is suppressed, the dielectric peak frequency dispersion phenomenon is aggravated, and the relaxation characteristics are gradually enhanced.

[0074] Fig.10 The bipolar hysteresis loops of the high entropy antiferroelectric ceramic materials in Examples 1-4 and Comparative Examples 1 and 2 are shown in the figure. As can be seen from the figure, when the La content x = 0, Comparative Example 1 exhibits ferroelectricity; after La begins to replace Bi (0.0 < x < 0.20), the high entropy ceramic begins to exhibit antiferroelectricity. Fig.11 Four current peaks appear in the ferrite. As the content of La replacing Bi increases, the high entropy ceramic gradually shows enhanced relaxation characteristics, while the turning electric field gradually increases, gradually showing enhanced relaxation antiferroelectricity.

[0075] Fig.11It is the current curve diagram of the high entropy antiferroelectric ceramic material in Examples 1-4 and Comparative Examples 1 and 2. It can be seen from the figure that with the increase of La replacing Bi content, the current peak of the current curve gradually decreases, the current peak gradually decreases and moves to the right, and shows a trend of broadening and gradually disappearing, indicating that the component regulation weakens the antiferroelectricity. When La completely replaces Bi (x=0.20), the antiferroelectricity disappears, and the high entropy ceramic shows a nearly linear hysteresis loop. The PE curve of the ceramic shows regular changes with the increase of La content, the relaxation characteristics are enhanced, the hysteresis loop becomes thinner, the residual polarization intensity gradually decreases, and the polarization response is significantly delayed.

[0076] Fig.12 The unipolar hysteresis loop diagrams of the high entropy antiferroelectric ceramic materials in Examples 1-4 and Comparative Examples 1 and 2 are shown in the figure. As can be seen from the figure, as the content of La replacing Bi increases, the energy storage density of the ceramic material increases with the increase of the electrical strength. The breakdown electric fields of Examples 1-4 are 527 kV·cm -1 、629kV·cm -1 、878kV·cm -1 and 716 kV·cm -1 , and the maximum energy storage density is 7.1 J·cm -3 , 9.0J·cm -3 、10.9J·cm -3 and 8.5 J·cm -3 .

[0077] Fig.17 The energy storage performance comparison diagram of the high entropy antiferroelectric ceramic materials in Examples 1-4 and Comparative Examples 1 and 2. As can be seen from the figure, the energy storage performance of the high entropy antiferroelectric ceramic material prepared in Example 3 (x = 0.14) reaches the optimal value, and the energy storage density and energy storage efficiency are 10.9 J·cm -3 , 86.2%.

[0078] Table 1 lists the key energy storage parameters of the ceramic samples obtained in Examples 1-4 and Comparative Examples 1-2, indicating that the high-entropy antiferroelectric ceramic materials (Examples 1-4) prepared by the present invention have the characteristics of high breakdown strength, high energy storage density and high energy storage efficiency, and have great application potential in the field of multilayer ceramic capacitors.

[0079] Table 1:

Claims

1. A high entropy antiferroelectric ceramic material with high energy storage performance, characterized in that: The composition chemical formula of the high entropy antiferroelectric ceramic material is: (Sr 0.2 Ca 0.2 Pb 0.2 Bi 0.2-x La x Na 0.2 )TiO3, where 0<x<0.

20.

2. The high entropy antiferroelectric ceramic material with high energy storage performance according to claim 1, characterized in that: x=0.10-0.16; preferably, x=0.

14.

3. The high entropy antiferroelectric ceramic material with high energy storage performance according to claim 1 or 2, characterized in that: The configuration entropy △S of the high entropy antiferroelectric ceramic material mix ≥1.61R.

4. The high entropy antiferroelectric ceramic material with high energy storage performance according to any one of claims 1 to 3, characterized in that: The breakdown electric field of the high entropy antiferroelectric ceramic material is 527-878 kV / cm; The recyclable energy storage density of the high entropy antiferroelectric ceramic material is 7.1-10.9 J / cm 3 ; The energy storage efficiency of the high entropy antiferroelectric ceramic material is 81.1% to 87.5%.

5. A method for preparing a high entropy antiferroelectric ceramic material with high energy storage performance according to any one of claims 1 to 4, characterized in that: include: (1) using strontium carbonate powder, calcium carbonate powder, lead oxide powder, bismuth oxide powder, lanthanum oxide powder, sodium carbonate powder, and titanium dioxide powder as raw materials, weighing and mixing according to the stoichiometric ratio of high entropy antiferroelectric ceramic materials, and pre-sintering to obtain ceramic powder; (2) grinding the obtained ceramic powder, adding a binder, and granulating, sieving and molding to obtain a ceramic green body; (3) The obtained ceramic green body is subjected to plastic disassembly and sintering to obtain the high entropy antiferroelectric ceramic material.

6. The preparation method according to claim 5, characterized in that: In step (1), the mixing method is ball milling; the parameters of the ball milling include: anhydrous ethanol as the ball milling medium, a ball milling speed of 200 to 240 rpm, and a time of 4 to 6 hours; The temperature of the pre-sintering treatment is 900-1000° C. and the time is 2-3 hours.

7. The preparation method according to claim 5 or 6, characterized in that: In step (2), the binder is a polyvinyl alcohol aqueous solution with a concentration of 6 to 7 wt.%; the amount of the binder added is 6 to 7 wt.% of the mass of the ceramic powder; The parameters of the fine grinding include: anhydrous ethanol as the ball milling medium, a rotation speed of 200 to 240 rpm, and a time of 4 to 6 hours; The sieve used for screening is 40 mesh.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In step (3), the temperature of the plastic discharge is 750-850°C for 2-3 hours; preferably, the temperature of the plastic discharge is 800°C for 2 hours; The sintering parameters include: a sintering temperature of 1100-1200° C., a sintering time of 2-3 hours, and a heating rate of 1-3° C. / min; preferably, the sintering heating rate is 2° C. / min.

9. An energy storage ceramic element, comprising: A high entropy antiferroelectric ceramic material with high energy storage performance as described in any one of claims 1 to 4, and an electrode distributed on the surface of the high entropy ceramic material.

10. Use of the high entropy antiferroelectric ceramic material with high energy storage performance according to any one of claims 1 to 4 in a multilayer ceramic capacitor.

Citation Information

Patent Citations

  • A-site high-entropy perovskite oxide and preparation method and application thereof

    CN110255610A

  • Antiferroelectric ceramic material and preparation method thereof

    CN111747739A

  • High-entropy lead-free energy storage ceramic material as well as preparation method and application thereof

    CN119118668A

  • Non-lead piezoelectric ceramic and piezoelectric, dielectric and pyroelectric element using the same

    JP2010095404A

  • Oxide body, piezoelectric device, and liquid discharge device

    US20080302658A1